ANALISIS SEMIOTIKA IKLAN JUDITH WILLIAMSON PADA FEED IG @JCOINDONESIA “COUNTING DAYS TO I LOVE JCO 2022” - Zaenudin Mukhtar (JURNAL Dasarrupa: Desain dan Seni Rupa, 2022)
This study seeks to explore the use of advertising semiotics in @jcoindonesia's feed design with the theme "COUNTING DAYS TO I LOVE JCO 2022". With the aim of knowing the messages and meanings represented through visual elements in the ad design on the @jcoindonesia Instagram feed which was uploaded on 27 June 2022. The method used in this research is qualitative. Process of the analysis is carried out using four scalpel semiotics of advertising initiated by Judith Williamson, namely product as signified, product as signifier, product as generator and product as currency. The results of this study are product as signifier indicated by script and sans serif fonts to represent personal closeness with customers who are generally upper middle-income consumers with modern lifestyles. Product as generator is shown through heart shapes, wavy lines, wavy organic shapes, as well as orange and brown colors to present a feeling of love, friendliness, joy and also reminds us of J.CO Donuts and Coffee's signature sweet, soft and tender donuts that whet the appetite. Product as currency is shown through product photos and displayed prices, the combination of visual elements contained in this ad design clearly shows that friendliness, closeness, tenderness and happiness are exchanges offered by products, and of course these products can be obtained at economical prices.